Self-Regulation, Conformity, and the Procrastination Puzzle: A Mediated Path Analysis Among University Students - Sarah Mafazah Daulay; Hasanuddin Hasanuddin; Salamiah Sari Dewi (Journal of Education on Social Science (JESS), 2025)
Academic procrastination undermines student achievement worldwide; yet, prior evidence on its antecedents focuses almost exclusively on individual-level self-regulation, while overlooking social pressures. This study investigates whether peer conformity mediates the relationship between self-regulation and procrastination among university students, thereby integrating cognitive-behavioural and sociocultural perspectives. A cross-sectional survey was administered to 428 undergraduates (Mage = 20.1 ± 1.4 years; 63 % female) recruited via stratified random sampling across four Indonesian universities. Participants completed validated Indonesian versions of the Short Self-Regulation Questionnaire, the Academic Procrastination Scale, and the Peer Conformity Scale. After confirmatory factor and reliability analyses, a latent-variable path model with a 5,000-sample bootstrap was tested in AMOS to estimate direct and indirect effects. The measurement model demonstrated good fit (χ²/df = 1.89, CFI = 0.962, TLI = 0.955, RMSEA = 0.046). Self-regulation negatively predicted conformity (β = −0.46, p < .001) and procrastination (β = −0.31, p < .001). Conformity positively predicted procrastination (β = 0.35, p < .001). A significant indirect path confirmed that conformity partially mediates the self-regulation–procrastination link (βindirect = −0.16, 95 % CI [−0.23, −0.10]), accounting for 34 % of the total effect. Findings extend social-cognitive models of delay behaviour by showing that low personal control heightens susceptibility to peer-norm pressures, intensifying procrastination. Interventions should pair self-regulatory training with strategies that recalibrate classroom norms (e.g., collaborative goal setting) to curb academic delay.